MISPERCEPTIONS OF COMMUNITIES IN POSYANDU - Atika Anggarsari; Sri Utami; Linda Dewanti; Bagus Setyo Boedi (Indonesian Midwifery and Health Sciences Journal, 2021)
AbstractBackground: Posyandu is a place for early detection of community-centred growth and development of toddlers. The March 2019 preliminary study resulted in a low coverage of the posyandu (D/S) participation rate in W Village, which was 32%. The purpose of this study was to determine the community's perception of the Posyandu activities for toddlers. Methods: This research is a descriptive qualitative research conducted in W Village. The sampling technique is purposive sampling. The number of informants consisted of 9 people. Data processing is data collection, data reduction, data presentation and conclusion drawing. Results: The results showed that the services provided by cadres and health workers were not optimal and there was a lack of infrastructure to support posyandu activities. Conclusion: The community interprets posyandu activities as only weighing and measuring height, which can actually be done by the community without having to play an active role in posyandu activities every month.